Dose-dependent Spasmolytic, Bronchodilator, and Hypotensive Activities of L. - Fatima Saqib; Arwa Abdulkreem AL-Huqail; Memona Asma; Liana Chicea; Mircea Hogea; Marius Irimie; Claudia Gavris (SAGE Publishing, 2022)
Panicum miliaceum L. is a medicinally effective plant used in indigenous system of medicine for a variety of ailments. However, there is no comprehensive study explaining its effectiveness in gastrointestinal tract, respiratory, and cardiovascular system ailments. This study was designed to validate the pharmacological basis for the folkloric use of Panicum miliaceum L. in diarrhea, asthma, and hypertension. Panicum miliaceum extract was analyzed to detect the presence of bioactive compounds by HPLC. The isolated rabbit jejunum, trachea, and aorta were used for in vitro experiments using tissue bath assembly coupled with Power Lab data acquisition system to explore their relative effects. In-vivo experiments were performed for anti-diarrheal activity. HPLC analysis revealed the presence of gallic acid, butylated hydroxytoluene, catechin, and quercetin. Concentration dependent activities were observed by relaxing K + (low) induced contractions having spasmolytic effect with EC50 = .358 ± .052, bronchodilator (EC50 = 2.483 ± .05793), and vasorelaxant (EC50 = .383 ± .063), probably due to the ATP dependent potassium channel activation. It was confirmed through pre-exposure of glibenclamide (specific ATP-dependent K + channel blocker) having similarities with cromakalim. Pm.Cr revealed its antidiarrheal via in vivo experiments on rats. This study indicates that Panicum miliaceum has antidiarrheal, spasmolytic, bronchodilator, and vasorelaxant activities probably due to the ATP dependent K + channel activation.